Strategi Kerja Sama Maritim India–ASEAN Menghadapi Ancaman Perang Modern - Dinesh Kumar Dhankhar; Yermia Hendarwoto; Jimmy Veni Tokio (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study examines the dynamics of maritime cooperation between India and ASEAN in addressing increasingly complex modern warfare threats, including cyberattacks, drone operations, non-state actors, and rising geopolitical tensions in the Indo-Pacific region. Using a qualitative descriptive approach—comprising interviews with naval officers from India and ASEAN member states, document analysis, and observation of activities such as CORPAT, Samudra Shakti, and the multilateral AIME exercise—the study finds that maritime cooperation has progressed through coordinated patrols, joint exercises, basic information exchanges, and the strengthening of institutional mechanisms such as the JDCC and SCMSC. However, the effectiveness of this cooperation remains limited by differences in command structures, technological gaps in MDA and C4ISR systems, and varying threat perceptions among ASEAN members. The findings indicate that although India–ASEAN maritime cooperation plays a crucial role in supporting regional stability, enhanced interoperability, standardized procedures, and integrated technology-based maritime surveillance systems are still required to effectively respond to the evolving challenges of modern warfare.